User Satisfaction with the Public Oral Health Services in the Different Dimensions of Health Care - Bordin, Danielle; Fadel, Cristina Berger; Saliba Moimaz, Suzely Adas [UNESP]; Saliba Garbin, Clea Adas [UNESP]; Santos, Celso Bilynkievycz dos; Saliba, Nemre Adas [UNESP] (Assoc Apoio Pesquisa & Saude Bucal-apesb, 2017)
Objective: To verify user satisfaction with the public oral health services in its different dimensions of care and relate them to the socioeconomic and demographic conditions. Material and Methods: Cross-sectional survey, developed with users interviewed of the public oral health services under the Primary Health Care of a Brazilian city (n=461). The associations of satisfaction with the socioeconomic and demographic conditions were analyzed using the chi-square test. Questions concerning satisfaction with the service were grouped into five domains-'physical structure', 'relation and communication', 'information and support', 'health care' and 'organization of services' analyzed using the Kruskal-Wallis Test. Results: Elderly individuals with low education and male, tended to be more satisfied with the services. The users reported being satisfied with the service, that were unhappy, referred to the time and the form to schedule a consultation, the time expected to be attended and the resolving capacity of oral health problems, as the causes. The overall satisfaction index was 0.8. The top rated domains were 'physical structure' (0.9) and 'relation and communication' (0.85). The ' service organization' domain received the worst evaluation (0.71) and when compared to the others domain presenting a significant difference. The 'physical structure' domain was significantly highlighted from the domains of 'oral health care' (0.78) and ' information and support' (0.78). The 'relation and communication' domain, also significantly excelled over the areas of 'oral health care'. Conclusion: The users rated the aspects of health care in a very positive way. The areas of highest user satisfaction were 'physical structure' and 'relation and communication'. However, the need for directing production processes in health became evident, especially regarding the organization of services, the domain with the worst rating.
Keywords: Dental Health Services; Oral Health; Primary Health Care